Currently used nucleic acid amplification tests for the detection of viruses and atypicals in acute respiratory infections - Ieven, Margareta (J Clin Virol, 2007)
For the detection of respiratory viruses conventional culture techniques are still considered as the gold standard. However, results are mostly available too late to have an impact on patient management. The latest developments include appropriate DNA- and RNA-based amplification techniques (both NASBA and PCR) for the detection of an extended number of agents responsible for LRTI. Real time amplification, the latest technical progress, produces, within a considerable shorter time, results with a lower risk of false positives. As results can be obtained within the same day, patient management with appropriate therapy or reduction of unnecessary antibiotic therapy in LRTI will be possible. A number of technical aspects of these amplification assays, and their advantages are discussed. The availability and use of these new diagnostic tools in virology has contributed to a better understanding of the role of respiratory viruses in LRTI. The increasing importance of the viral agents, Mycoplasma pneumoniae and Chlamydophila pneumoniae in ARI is illustrated. A great proportion of ARI are caused by viruses, but their relative importance depends on the spectrum of agents covered by the diagnostic techniques and on the populations studied, the geographical location and the season. The discovery of new viruses is ongoing; examples are the hMPV and the increasing number of coronaviruses. Indications for the use of these rapid techniques in different clinical situations are discussed. Depending on the possibilities, the laboratory could optimize its diagnostic strategy by applying a combination of immunofluorescence for the detection of RSV an IFL, and a combination of real-time amplification tests for other respiratory viruses and the atypical agents. When implementing a strategy, a compromise between sensitivity, clinical utility, turn around time and cost will have to be found.